Effect of pH on hydrogen pick-up and corrosion of Zircaloy-4 - Sayers, J (2017)
This thesis was part of the MUZIC-2 collaboration and describes the effect of different water chemistries on the corrosion and hydrogen pick-up in Zircaloy-4. Samples of Zircaloy-4 were oxidised in an autoclave containing pure water at 360°C (pH360 = 6.15) and at 350°C in an elevated pH (pH350 = 8.82, with 50% deuterated water) compared to commercial reactors. They were examined by scanning transmission electron microscopy (STEM), Thermal Desorption Spectroscopy (TDS) and Secondary Ion Mass Spectroscopy (SIMS). There was a change in the oxidation rate for the samples exposed to different environments, in part from the difference in the oxidation temperature and in part due to the pH of the oxidising environment, although it is the elevated pH which has a lower oxidation rate in the pre-transition regime. The oxide-metal (OM) interface was characterised along with second phase particles (SPPs) present in the metal and the oxide. It was found that the region of oxygen-saturated zirconium (OSZ) and ZrO follow a cyclical growth pattern which has the same periodicity as the advance of the OM interface. The OSZ gradually thickens as the oxidation rate decreases in the late pre-transition period, before disappearing after transition and then growing again in the second cycle of oxidation. The thickness of the layers formed appears to be independent of the pH used in the experiments. The oxidation of Fe and Cr and the Fe/Cr ratio in SPPs were examined. The SPPs were oxidised after the surrounding Zr oxidised. The Fe/Cr content in the middle of the SPPs decreased quickly as the Fe was found to migrate towards cracks formed at the edge of SPPs. Cr migrated much more slowly towards the cracks than Fe and oxidised before Fe. The hydrogen/deuterium content of the samples was measured with TDS. Two characteristic desorption peaks for hydrogen have been found at ~350°C and ~650°C. The latter occurs when the difference in free energy between hydrogen in the metal and in the gas phase becomes positive. There is a delay to the desorption when an oxide layer is present, until the temperature reaches the point at which it is dissolved into the metal, allowing the hydrogen to desorb. The hydrogen pick-up during the first 1.5 µm of oxide growth was similar for both environments. For thicker oxides the samples exposed to pure water showed four times the amount of hydrogen pick-up compared to the high pH samples. The modelling of hydrogen desorption from Zr was carried out using the Tritium Migration and Analysis Program (TMAP). It was possible to replicate the low temperature peak with the literature values for the binding energy of hydrogen with Zr and the hydrogen diffusion activation energy (ED), but for the high temperature peak the required ED was higher than the literature value. An attempt at modelling both peaks simultaneously is shown.